2
$\begingroup$

I need to prove that $n^3 - n$ is divisible by $6$ by factoring it and by knowing that the product of each consecutive $3$ numbers is divisible by $2$ and $3$. I tried:

$n(n^2 - 1)$

Factoring it didn't really get me anywhere. I think I'm supposed to do something like:

$n[(n - 1)(n - 2)]$ And if I do the math in this I get back:

$n[n^2 - 3n + 2] = n^3 - 3n^2 + 2n$

which looks like a dead end, unless I can somehow prove that:

$n^3 - n = n^3 - 3n^2 + 2n$

But that's impossible, since it's not true that $2n^2 = 2n$ for every positive integer

So what else can I do? These are the instructions the book gave - factor it and remember that the product of three consecutive number is divisible by 6.

$\endgroup$
2
  • 1
    $\begingroup$ Hint: $n^2-1=(n-1)(n+1)$ $\endgroup$ – Guest Dec 5 '14 at 22:12
  • $\begingroup$ In general, the product of k consecutive numbers is always divisible by $k!$. $\endgroup$ – Lucian Dec 6 '14 at 2:44
8
$\begingroup$

You were on the right track initially.

$$n^3-n = n(n^2-1) = n(n+1)(n-1).$$

These are three consecutive integers, so at least one of them is even. Additionally, $3$ must divide one of the numbers by the same logic. Thus $n^3-n$ is divisible by $6$ since it is divisible by $2$ and $3$.

$\endgroup$
1
$\begingroup$

Hint:$(n^2-1)=(n+1)(n-1)$, so $$ n(n^2-1) = (n-1)n(n+1)$$

And because $6 = 2 \cdot 3 \wedge \gcd(2,3)=1$

$$6 \mid n \Longleftrightarrow 2 \mid n \wedge 3 \mid n $$

You should note too, that one of two numbers has to be even.

$$(\forall n \in \mathbb{Z})(2 \mid n~ \dot\vee ~2 \mid (n+1))$$

And similarly you can show divisible by three ($3$ has to divide one of three consecutive numbers).

If you want long explanation you can say: the remainder ($n \mod 3$) is $0$, then $3\mid n$, otherwise the remainder can be $2$ and $3 \mid (n+1)$ or $1$ and then $3 \mid (n+2)$. So $$(\forall n \in \mathbb{Z})\left(3 \mid (n-1)~ \dot\vee ~ 3 \mid n~ \dot\vee ~3 \mid (n+1)\right)$$


Pursuant to above claims.

$$\begin{split} (2 \mid n ~\dot\vee~ 2 \mid (n+1))\wedge (3 \mid (n-1) ~\dot\vee~ (3 \mid n) ~\dot\vee~ 3 \mid (n+1)) &\Longleftrightarrow\\ \left(2 \mid n(n^2-1) \wedge 3 \mid n(n^2-1)\right)&\Longleftrightarrow 6 \mid n(n^2-1) \end{split}$$

$\mathscr{Q.E.D.}$

$\endgroup$
0
$\begingroup$

$$N^3-N = N \cdot (N^2-1) = N \cdot (N-1) \cdot (N+1)$$

$N-1, \;N$ and $N+1$ have to be three consecutive numbers as $N$ is constant.

If you have three numbers, at least one of them has to have a factor of $2$ and one of them has a factor of $3$.

Since both $2$ and $3$ are factors, $\operatorname{lcm}(2,3)=6$ is also a factor.

$\endgroup$
1
  • $\begingroup$ Please use latex to write the answer $\endgroup$ – Isaac YIU Math Studio Nov 16 '19 at 15:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.